Carbohydrate Conjugates in Vaccine Developments - Lang, Shuyao; Huang, Xuefei (Frontiers in Chemistry, 2020)
Vaccines are powerful tools that can activate the immune system for protection against various diseases. As carbohydrates can play important roles in immune recognition, they have been widely applied in vaccine development. Carbohydrate antigens have been investigated in vaccines against various pathogenic microbes and cancer. Polysaccharides such as dextran and β-glucan can serve as smart vaccine carriers for efficient antigen delivery to immune cells. Some glycolipids, such as galactosylceramide and monophosphoryl lipid A, are strong immune stimulators, which have been studied as vaccine adjuvants. In this review, we focus on the current advances in applying carbohydrates as vaccine delivery carriers and adjuvants. We will discuss the examples that involve chemical modifications of the carbohydrates for effective antigen delivery, as well as covalent antigen-carbohydrate conjugates for enhanced immune responses.